ANALISIS KEWENANGAN GUBERNUR DKI JAKARTA DALAM MENETAPKAN KEPUTUSAN UPAH MINIMUM PROVINSI TAHUN 2022: Analysis of the Authority Governor of DKI Jakarta in Provincial Minimum Wage Decision for the Year 2022 - Sandy Maulana Yusuf Saidi; Tri Sulistyowati (Faculty of Law, Universitas Trisakti, 2024)
This study is based on previous work by the Governor of DKI Jakarta, who, in his 2021 Decree No. 1359, first decided on a minimum salary by looking at government regulations pertaining to salaries. Afterwards, Decree Number 1517 superseded it, disregarding the applicable government wage regulations. Examining whether or not Governor DKI Jakarta's Decision Number 1517 of 2021, which sets the minimum salary for 2022, conforms with legal requirements, and whether or not the Governor has the jurisdiction to decide minimum wage choices based on extant legislation are the problems that this study seeks to address. Using secondary data culled from a variety of sources, including main legal resources like statutes and secondary legal materials like books and journals, this study takes a descriptive-analytical method. Qualitative research and inference led to the conclusion that Law 23 of 2014 on Regional Governments grants the Governor of DKI Jakarta the authority to establish the provincial minimum salary for 2022. Unfortunately, this decision was not made in accordance with the processes laid forth in Law No. 12 of 2011 on the Formation of Legal standards.